Criminal Law Policy of Justice Collaborator in Corruption Crime Case - Khrisna Lintang Satrio Nugroho (LAW REFORM, 2021)
Trial of criminal law cases is highly important to prove misconduct in a case. In respect to the evidence of corruption criminal act, an insider is needed as a perpetrator of the offence who works with the investigators, or usually called justice collaborator. The main focus of this study is to examine criminal law policy on the concept of justice collaborator in corruption criminal act and how the legal punishment is for justice collaborators in corruption criminal act. This study is a descriptive research using juridical normative approach. Data used in this study were secondary data. Case study approach was applied in this study. This means that the researcher makes a comparison of cases on the implementation of justice collaborator which is based on a study of a verdict.  According to the result of the research, it is indicated that up to now there has not been conformity in terms of legal regulations or interpretation of the concept of Whistle blower and Justice Collaborator. There has not been mutual understanding in terms of the conviction of the perpetrator who is willing to work with the investigators to uncover a corruption criminal act. This leads to disparity in the making of verdict for the offender.